PENGARUH TERAPI RELAKSASI AUTOGENIK TERHADAP KUALITAS TIDUR PADA LANSIA DI PANTI SOSIAL RUMOH SEUJAHTRA GEUNASEH SAYANG ULEE KARENG KOTA BANDA ACEH - Lidayani, Wilda; Sartika, Dewi; Iskandar, Iskandar (NUCLEUS, 2024)
Aging is a stage in life marked by a decline in the body’s ability to adapt to its surroundings, leading to various health issues, including impaired sleep quality. One non-pharmacological intervention to address sleep disturbances is autogenic relaxation therapy, which helps modulate physiological responses and can enhance sleep quality for elderly. This study aimed to assess the impact of autogenic relaxation therapy on the sleep quality of elderly residents at the Rumoh Seujahtra Geunaseh Sayang Social Home in Ulee Kareng, Banda Aceh. This pre-experimental research employed a one-group pretest-posttest design. The population consisted of 59 elderly individuals, with a purposive sampling technique used to select a sample of 37 participants. Data were collected using a structured questionnaire. The study was conducted from May 17-19, 2024, at the Rumoh Seujahtra Geunaseh Sayang Social Home. The findings revealed that prior to the intervention, the majority of participants (78.9%, or 29 respondents) had poor sleep quality, while after receiving autogenic relaxation therapy, 59.5% (22 respondents) exhibited good sleep quality. Statistical analysis using the non-parametric Wilcoxon test showed a significant improvement in sleep quality with a p-value of 0.000 (p < 0.05). The study concluded that autogenic relaxation therapy has a positive effect on improving sleep quality in the elderly at the Rumoh Seujahtra Geunaseh Sayang Social Home, Ulee Kareng, Banda Aceh. It is recommended that elderly residents incorporate autogenic relaxation therapy into their routines to enhance sleep quality.